Assessment of photobiomodulation combined with new restorative material for teeth with molar incisor hypomineralization on control of hypersensitivity and longevity of restorations: Protocol for a randomized controlled blind clinical trial - Caroline Diniz Pagani Vieira Ribeiro; Amanda Rafaelly Honório Mandetta; Fabiana Car Pernomiam; Caroline Cristina Batista De Camargo; Iara Maria Freitas Romano; Ana Paula Taboada Sobral; Marcela Letícia Leal; Raquel Agnelli Mesquita-Ferrari; Kristianne Porta Santos Fernandes; Anna Carolina Ratto Tempestini Horliana; Lara Jansiski Motta; Cinthya Cosme Gutierrez Duran; et al. (PLoS ONE, 2025)
Molar incisor hypomineralization (MIH) is a qualitative defect of enamel development that occurs in the mineralization phase. MIH affects one or more permanent molars and, occasionally, permanent incisors. The aim of the proposed study is to determine whether photobiomodulation combined with a new self-cure resin improves hypersensitivity in molars with MIH (primary outcome). Secondary outcomes include assessing the clinical performance of the self-cure composite resin in terms of restoration longevity and comparing the effectiveness of three interventions—photobiomodulation combined with self-cure resin, self-cure resin alone, and photobiomodulation combined with bulkfill photopolymerizable resin—in controlling hypersensitivity over time. Permanent molars with MIH in patients 6–10 years of age will be allocated to three groups. Group 1: photobiomodulation + self-cure composite resin restoration; Group 2: self-cure composite resin restoration; Group 3: photobiomodulation + restoration in bulk-fill photopolymerizable composite resin. Photobiomodulation will be performed in a single session involving low-level laser administered to four different points. The laser will be used at a wavelength of 808 nm, power of 100 mW and energy of 1 J per points; irradiance will be 3571 mW/cm2, with a total radiant exposure of 35.7 J/cm2. Data normality will be checked using the Shapiro-Wilk test, and variance homogeneity will be assessed with the Levene test. Descriptive statistics will be used to present the data, with continuous variables expressed as mean and standard deviation, and categorical variables by relative frequency. To compare the Wong-Baker Faces Pain Rating Scale and SCASS scales, repeated measures ANOVA will be employed, considering the 3 groups and 5 time points. Bonferroni adjustment will be applied for post-hoc comparisons. Sphericity will be tested with Mauchly’s test, and if violated, Greenhouse-Geisser correction will be applied. A significance level of 0.05 will be adopted. Trial registration ClinicalTrials.gov NCT06538142